Extracellular Vesicles Derived From Trichinella spiralis Muscle Larvae Ameliorate TNBS-Induced Colitis in Mice - Yang, Yong; Liu, Lei; Liu, Xiaolei; Zhang, YuanYuan; Shi, Haining; Jia, Wanzhong; Zhu, HongFei; Jia, Hong; Liu, Mingyuan; Bai, Xue (Frontiers in Immunology, 2020)
Helminths are masters at modulating the host immune response through a wide variety of versatilemechanisms. These complex strategies facilitate parasite survival in the host and can also be exploited to prevent chronic immune disorders by minimizing excessive inflammation. Extracellular vesicles (EVs) are small membrane-bound structures secreted by helminths which mediate immune evasion during parasite infection. The goal of this study was to investigate the immunoregulatory properties of Trichinella spiralis EVs (Ts-EVs) in a murine model of colitis. We found that Ts-EVs significantly ameliorated 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice. Ts-EVs alleviated intestinal epithelium barrier damage, markedly reduced pro-inflammatory cytokine secretion and neutrophil infiltration, and upregulated immunoregulatory cytokine expression in colon tissue. Ts-EVs also modulated the adaptive immune response by influencing T-cell composition. The numbers of Th1 and Th17 cells in MLNs, as well as the expression levels of Th1/Th17-associated cytokines and transcription factors in colon were reduced. In contrast, Th2 and Treg cells were increased after Ts-EVs treatment. Furthermore, sequencing of EV-derived microRNAs (miRNAs) indicated that an array of miRNAs was involved in the regulation of the host immune response, including inflammation. These findings expand our knowledge of host-parasite interactions, and may help design novel and effective strategies to prevent parasite infections or to treat inflammatory diseases like IBD. Further studies are needed to identify the specific cargo molecules carried by Ts-EVs and to clarify their roles during T. Spiralis infection.